Biomarkers of Inflammation in Asthma: A Clinical Perspective - Taylor, D. Robin (Seminars in Respiratory and Critical Care Medicine, 2012)
Asthma is a heterogeneous disease, with wide variability in pathology, natural history, and response to therapy. Historically, treatment of asthma relied almost exclusively on clinical judgment and pulmonary function tests (spirometry or peak flows), despite the limitations of both. Physiological tests are one step removed from what the clinician needs to know, namely, the underlying activity and whether it is amenable to additional or alternative treatment. Within the past decade, categorization of different pathological phenotypes and the treatment-response phenotypes have been used to guide therapy. Additionally, biomarkers (particular induced sputum analysis and exhaled nitric acid) have been tests to assess disease “activity” and predict potential response (or lack of response) to therapy. Currently, the value of biomarkers from exhaled air or airway fluids remains controversial. Clinical utility is dependent on the performance characteristics in relation to specific clinical questions. Financial constraints applied by health providers and funding agencies have limited the use of induced sputum analysis and exhaled nitric oxide to date. However, evaluation of candidate biomarkers has provided important insights in clinical practice and in research settings. At the very least, existing techniques should have a regular place in severe asthma clinics, if not more widely, where heterogeneity is the norm and not all asthma is what it seems.
Keywords: asthma; biomarkers; exhaled nitric oxide